The Four Problems which Old Testament Married Couples Grapple with - Marcin Majewski (Polonia Sacra, 2018)
In the context of a lively debate on the encyclic of Pope Francis Amoris laetitia, in this article I take up the four most important problems that marriages in the Old Testament grappled with: polygamy, or marrying multiple spouses, lack of offspring, infidelity, or betrayal, and divorce. It is only against this issues that the profound novum of Catholic teaching on marriage emerges. The proposal will be that problems afflicting couples of biblical time are not so different from the ones besetting contemporary couples.